2020
DOI: 10.1111/jvim.15949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcifediol supplementation on markers of chronic kidney disease‐mineral and bone disorder in dogs with chronic kidney disease

Abstract: Background: Chronic kidney disease-mineral and bone disorder (CKD-MBD) in dogs is associated with hypovitaminosis D, increased parathyroid hormone (PTH), and increased fibroblast growth factor-23 (FGF-23) concentrations. Best practice for vitamin D metabolite supplementation in CKD-MBD remains unknown. Objective: To provide an extended-release calcifediol supplement to dogs with CKD and to measure its effects on variables indicative of CKD-MBD. Animals: Ten dogs with International Renal Interest Society stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…One unpublished study found that judicious administration of 1,25(OH) 2 D may confer a survival benefit in dogs with IRIS stages 3 and 4 providing calcium, phosphate and PTH can be closely monitored (Polzin et al 2005). A recent study found that administering an extended release form of 25(OH)D to dogs with CKD resulted in an increase in vitamin D metabolites, including 1,25(OH) 2 D, while avoiding hypercalaemia (Parker et al 2020). However, the benefits of long-term 25(OH)D supplementation on the progression of CKD, and the patient's quality of life, remained undetermined in this study (Parker et al 2020).…”
Section: Urinary Tract Diseasementioning
confidence: 61%
See 1 more Smart Citation
“…One unpublished study found that judicious administration of 1,25(OH) 2 D may confer a survival benefit in dogs with IRIS stages 3 and 4 providing calcium, phosphate and PTH can be closely monitored (Polzin et al 2005). A recent study found that administering an extended release form of 25(OH)D to dogs with CKD resulted in an increase in vitamin D metabolites, including 1,25(OH) 2 D, while avoiding hypercalaemia (Parker et al 2020). However, the benefits of long-term 25(OH)D supplementation on the progression of CKD, and the patient's quality of life, remained undetermined in this study (Parker et al 2020).…”
Section: Urinary Tract Diseasementioning
confidence: 61%
“…A recent study found that administering an extended release form of 25(OH)D to dogs with CKD resulted in an increase in vitamin D metabolites, including 1,25(OH) 2 D, while avoiding hypercalaemia (Parker et al 2020). However, the benefits of long-term 25(OH)D supplementation on the progression of CKD, and the patient's quality of life, remained undetermined in this study (Parker et al 2020).…”
Section: Urinary Tract Diseasementioning
confidence: 61%
“…Supplementation with 25(OH)D (30 or 60µg/animal/day) continuously or intermittently in nephropathic dogs was able to increase the mean serum concentration of 25(OH)D by 470% and calcitriol mean serum concentration by 94% until the 84th day of therapy, without signs of toxicity. However, no beneficial effects of this supplementation on disease progression or manifestation of clinical signs were noted until the end of the work (Parker et al, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…Low concentration of this vitamin has been associated with several diseases, including chronic and infectious illnesses (Corbee, 2020;Weidner & Verbrugghe, 2017). In humans, vitamin D deficiency has been related to obesity and type II diabetes (Bouillon et al, 2014), while in dogs and cats an association has been made with gastroenteric, cardiovascular and renal diseases (Allenspach et al, 2017;Kraus et al, 2014;Parker et al, 2020). Several diseases in companion animals also promote disturbances in vitamin D metabolism and therefore vitamin D status evaluation may be useful as a prognostic predictor (Weidner & Verbrugghe, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since all vitamin D is essentially converted to 25(OH)D and this metabolite is found abundantly in circulation, it is the most commonly measured indicator of vitamin D status ( 18 ). Circulating 25(OH)D 3 is an active metabolite and has been found to be more potent at influencing vitamin D status than vitamin D 3 when administered as a supplement to dogs ( 19 , 20 ), rats ( 21 , 22 ), chicks ( 21 ), and humans ( 23 , 24 ). In fact, 25(OH)D 3 is reported to be up to 10 times more potent than vitamin D 3 in humans ( 23 ) and may prove an effective form of supplementation for people and animals in diseases such as chronic kidney disease and cardiovascular disease ( 23 , 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%